THE EFFECT OF GUIDED NOTE TAKING LEARNING STRATEGY ON STUDENTS’ LEARNING INTEREST ON ECOSYSTEM MATERIAL AT VII CLASS - Kurratul 'Aini; Amilda .; Awalul Fatiqin; A Zulaiha (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This study aims to determine the effect of applying Guided Note Taking to the interest of learning on theecosystem material at VII Class. This research design used posttest-only control design with true experimentalmethod. The sample of this research was 35 students. Based on the result, the student interest analysis showedthat the implementation of learning in the experimental class by applying Guided Note Taking is better than thelearning in the control class that was not applying the Guided Note Taking. This can be seen from thecalculation of t-test with a significant level of 5% with tarithmetic˃ ttable or 11,38 ˃ 1,670; Ha is accepted and H0 isrejected. The result of the average score analysis of the students' learning interest in the experimental class is73,17 while the students' interest in the control class is 58.6, which means that the students' learning interest ishigher than the students' interest in the control class. Thus, it can be deduced that the Learning Strategy typeGuided Note Taking influences the students' learning interest on Ecosystem Material in VII Class. Keywords: learning strategy, guided note taking, learning interest, ecosystem